لجوء القضاء الإداري لنظريات ومبادئ العقد المدني في مجال الصفقات العمومية - إيراين، نوال; شريف، سمية Sherif, Sumayah (جامعة محمد خيضر بسكرة - كلية الحقوق والعلوم السياسية - مخبر أثر الاجتهاد القضائي على حركة التشريع, 2022)
تقوم العقود الادارية ومنها الصفقات العمومية -ككل عقد-على توافق إرادتين بقصد إنشاء آثار قانونية، فتستند أساسا على ركن الرضا، فمبدئيا يمكن القول إن العقد الإداري شريعة المتعاقدين، يعد التعارض بين عقود القانون العام وعقود القانون العام أمرا مبالغا فيه، فالطبيعة الذاتية للعقد في الحالتين، تستدعي حدا أدنى من الوحدة بينهما، وأن نظامهما القانونيان غير متعارضين بصورة جذرية دائما، فهما يشتركان في شروط تكوينهما. عرفت مرحلة تنفيذ الصفقة العمومية بدورها إعمال نظريات القانون الخاص فلم يجد القاضي الإداري أي حرج في إعمال النظريات ذات الأصل المدني ومن أبرزها؛ نظرية القوة القاهرة، نظرية الاثراء بلا سبب فضلا عن آلية المقاولة الفرعية أو المناولة. Administrative contracts, including public deals as any deal are based on the agreement of two wills with the intention of creating legal effects, and they are mainly based on the corner of consent. In principle, it can be said that the administrative contract is the deal of contractors. The contradiction between public law contracts and private law contracts is an exaggerated nature. The contract in both cases requires a minimum of unity between them, and their legal systems are not always radically in conflict, as they share the conditions of their formation. The stage of implementing public deals in turn defined the implementation of private law theories, so the administrative judge did not find any embarrassment in implementing theories of civil origin, most notably: force majeure theory, the theory of enrichment without cause, as well as the mechanism of sub-contracting or handling.
Keywords: القانون الإداري -- الصفقات العامة -- الإلتزامات التعاقدية -- المسؤولية المدنية -- السلطة القضائية